2018
DOI: 10.2528/pierl18042203
|View full text |Cite
|
Sign up to set email alerts
|

Design of Printed Monopole Antenna for Wireless Energy Meter and Smart Applications

Abstract: European smart energy meter applications operate over a smart grid network. These applications operate over ISM frequency bands. The proposed dual-band printed monopole antenna provides a solution to smart energy meter applications. The surface dimension of the planar monopole antenna is 45×17 mm 2. The antenna has strips fabricated on a standard cost-effective FR-4 substrate of thickness 1.6 mm for achieving dual-mode resonance at 868 MHz and 2.4 GHz. The proposed monopole antenna has operating impedance band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The proposed geometry offers better gain than the configurations in [1,5,14] in the higher bands for a much smaller overall dimension. As far as the lower band is concerned, gain is moderate, but the proposed geometry is of smaller dimension than [15,16]. The realized peak gains in the bands are 0.136, 2.12 and 3.55 dBi, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The proposed geometry offers better gain than the configurations in [1,5,14] in the higher bands for a much smaller overall dimension. As far as the lower band is concerned, gain is moderate, but the proposed geometry is of smaller dimension than [15,16]. The realized peak gains in the bands are 0.136, 2.12 and 3.55 dBi, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Different techniques, such as slot loaded patch, meander lines, stacked layers, parasitic elements, defects in ground structure (DGS), Metamaterial structures [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], are used for exciting the antenna at multiple frequencies. In slot loading technique, appropriately placed slots in the resonating patch with different shapes like inverted U [1][2][3], I [4], hexagon [5], circular [6], and L shape [7] are effectively used to produce additional bands.…”
Section: Introductionmentioning
confidence: 99%
“…Planar multiband antenna has attractive design properties viz. low profile and ease in fabrication, hence planar monopole antennas are utilized extensively in handheld devices such as mobile phones, tablet computers, and laptops [3][4][5]. The fundamental cause of this over dependency is due to flexibility in the resonator design.…”
Section: Introductionmentioning
confidence: 99%
“…Patel et al demonstrated effective use of L and U‐shaped slots defects introduced in the ground plane for providing reactive components internally to produce additional bands. In Reference , a hook‐shaped metal strip antenna with 1 mm slot at the middle to connect a lumped element switch is proposed. It can operate either in 2.45/5.13 GHz bands or in 3.49/5.81 GHz bands based on ON/OFF status of the switch.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed compact printed monopole antenna consists of Inverted L slot, Pi‐shaped slot and a truncated square patch at left corner for triple‐band operations. The proposed slot antenna has a small size with high peak gain as compared to antennas presented in Reference and has a simple geometry, covering required WLAN/WiMAX bands.…”
Section: Introductionmentioning
confidence: 99%